Volume 8: Ocean Renewable Energy 2022
DOI: 10.1115/omae2022-80986
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on a Speed Controlled Wells Turbine for Wave Energy Conversion

Abstract: Ocean wave energy represents one of the most attractive renewable sources due to its high availability and predictability. Solutions based on the Oscillating Water Column (OWC) principle are one of the most promising for sea-wave energy conversion. The system is composed of two main units, an open chamber that converts the sea wave motion into an alternating airflow, and a turbine driven by this flow. The typical alternating airflow inside the OWC chamber requires a turbine with self-rectifying behavior. The W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…43 Therefore, speed adjustment with accurate control strategies can broaden the stall margin and avoid the degradation of turbine performance. 44,45…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Therefore, speed adjustment with accurate control strategies can broaden the stall margin and avoid the degradation of turbine performance. 44,45…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…43 Therefore, speed adjustment with accurate control strategies can broaden the stall margin and avoid the degradation of turbine performance. 44,45 The streamline distribution at a 90% span of the incipient stall point (peak torque coefficient point) is displayed in Figure 7. It is worth noting that although the incipient stall point is slightly different under various tip gap and speed combinations, the Reynolds number at the same speed is almost the same.…”
Section: Global Performance Analysismentioning
confidence: 99%
“…The effectiveness of the control action with respect to the stalled conditions is evident, with an increase of about 100% for the turbine overall average efficiency. If the same speed control strategy is applied to the Wells turbine when the operating conditions are not affected by stall, efficiency improvements have been observed to be lower [18], in the order of 2-4%. An open-loop control strategy was chosen and applied iteratively in order to take into account that the pressure drop through the turbine, which was used to predict the control law, varies with the operating conditions.…”
Section: Control Phase Resultsmentioning
confidence: 99%
“…It should be observed that the operating condition selected for the present investigation (the red cross) falls in the stable region, before the stall point, with a safe distance from the latter in order to avoid incipient stall conditions on the blade that are associated with local flow separations which are not investigated in this work. The selected operating condition, i.e., with φ ≈ 0.195, is characterized by a turbine global efficiency of 48.1%, which is near its maximum, as it can be evinced from Licheri et al [21].…”
Section: Measuring Techniquementioning
confidence: 99%